Pemikiran Ki Hadjar Dewantara Dan Kebijakan Merdeka Belajar - Yan Nurcahya; Widiati Isana; Deri Sugiarto; M Kautsar Thariq Syah (Yayasan Al-Afif, 2025)
Ki Hadjar Dewantara through Taman Siswa has inherited the embryo of an education system based on local Indonesian culture. Teaching in Taman Siswa is based on two main principles, namely among and pamong. The principle of among places students as the main target and priority that must be